Vivir la violencia materna : la voz de los niños y las niñas (2011)
ABSTRACT: This article provides information regarding the meaning that a group of sons and daughters place in their affective bonding with their mothers, who consider themselves mistreating mothers. Method: a phenomenological-hermeneutic method following a qualitative-comprehensive approach with multilevel sampling. Data generation techniques for the general study: in-depth interviews with mothers, and focus groups with their children. We also used focus groups with parents from three different educational institutions. It was there where we developed the findings obtained from using the focal groups technique with the children. Conclusions: we conclude that (1) maternal violence creates a communication style based on a disagreement of bonds; (2) children who believe they can “bend destiny” have some strategies for withstanding maternal violence; (3) the feeling of recognition and belonging to a weave of bonds builds resilience in children; and (4) this study confirms the importance of a third party that regulates maternal violence.